Natural Paste for Textile Prints - Nazlina, Shaari; Khairul Aidil Azlin, A. Rahman (Universiti Malaysia Sarawak (UNIMAS), 2014)
In the Malaysian textile industry, synthetic print pastes are used extensively in the process of designing surface fabrics. Each printing method requires a paste or thickening agent with special characteristics, frequently referred to as flow characteristics. The synthetic thickening agents used are generally extremely highmolecular-weight polymers capable of developing a very high viscosity at a relatively low concentration. However, the paste or thickening are difficult to dispose that create sedimentation to the water during disposal of its wastes. It will be discharged into the drain and rivers that will affect the quality of water and environment. The research explores instances where printing producers and artist can use starch as a thickening agent or paste for unique qualities in textile printing. As an alternative to synthetic pastes, natural biodegradable materials developed from sago can be used during printing process. The advantages of this product are environmental friendly that is non-toxic fumes; production cost is lower, instance application and a creative process enhancement in textiles production.